A Study on Colour Combination Guidelines for Text and Background in Web Legibility Perspective - Ahmad Affendi, Hashim; Mazlina, Abdul Majid (2013)
Nowadays, webpages are widely used to disseminate information or as an online application to replace the old paper based form. Since webpages are flexible and simple for the web developer to design and use a variety of colour combinations, font types and font sizes, guidelines seem very important in helping a web designer to design an aesthetically appealing and legible webpage. However, the guidelines developed are based on earlier research that was mostly done using old Video Display Technologies (VDT). The latest generation of VDT is capable of displaying sharper images with its high-resolution technologies. The differences in the display technologies have made this area of research very important for a restudy. This paper will explore the current guidelines and determine what is necessary to ensure web text legibility through choosing the right colour combinations to be used as well as fonts and background colour.